2014
DOI: 10.1130/g35920.1
|View full text |Cite
|
Sign up to set email alerts
|

Latest Permian chars may derive from wildfires, not coal combustion

Abstract: 7The Permian-Triassic extinction event was the largest biocrisis of the Phanerozoic. One 8 of the principle triggers for the 'big dying' is thought to be greenhouse warming resulting from 9 the release of CH 4 from basalt-coal interaction during the extensive Siberian Trap eruptions. 10Observations of organic matter interpreted to be coal combustion products (fly ash) in latest 11Permian marine sediments have been used to support this hypothesis. However, this 12 interpretation is dependent upon vesicular char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The lower cloud optical depth as simulated in this study leads to a global average temperature increase of 4.5 °C, with extreme regional temperatures of >38 °C in the Tethys Ocean (Joachimski et al, 2012;2014) and >50 °C on land and an increase in vertical stratification in the ocean, resulting in an expansion of the oxygen minimum zone and low oxygen environments (Hallam and Wignall, 1997;Isosaki et al, 1997;Knollet al, 1996;Ward et al,2001;Wignall et al, 1996;Hallam, 1992, 1993;Wignall and Newton, 2003;Wignall and Twitchett, 2002). The processes described above act on relatively short timescales,with low productivity during the early Triassic (in the aftermath of the PTB extinction) resulting in reduced DMS emissions, thus favoring lower CCN concentrationsand hothouse conditions during that time.On longer timescales,however, an increase in the marine nutrient inventory due to weathering intensification by global warming, increased rain fall, and acid rain (Black et al, 2014), followed by soil erosion (Sephton et al, 2005) that is also enhanced by forest fires (Hudspith et al, 2014),would ultimately lead to enhanced marine productivity (Algeo et al, 2011)and anoxia (Meyer et al, 2008;Winguth and Winguth, 2012;Grasby et al, 2013).An associated rise in DMS emissions from the ocean and the resulting increase in cloud albedo by higher CCN concentrations would counteract the warming and weathering (Fig. 10).…”
Section: Discussionmentioning
confidence: 99%
“…The lower cloud optical depth as simulated in this study leads to a global average temperature increase of 4.5 °C, with extreme regional temperatures of >38 °C in the Tethys Ocean (Joachimski et al, 2012;2014) and >50 °C on land and an increase in vertical stratification in the ocean, resulting in an expansion of the oxygen minimum zone and low oxygen environments (Hallam and Wignall, 1997;Isosaki et al, 1997;Knollet al, 1996;Ward et al,2001;Wignall et al, 1996;Hallam, 1992, 1993;Wignall and Newton, 2003;Wignall and Twitchett, 2002). The processes described above act on relatively short timescales,with low productivity during the early Triassic (in the aftermath of the PTB extinction) resulting in reduced DMS emissions, thus favoring lower CCN concentrationsand hothouse conditions during that time.On longer timescales,however, an increase in the marine nutrient inventory due to weathering intensification by global warming, increased rain fall, and acid rain (Black et al, 2014), followed by soil erosion (Sephton et al, 2005) that is also enhanced by forest fires (Hudspith et al, 2014),would ultimately lead to enhanced marine productivity (Algeo et al, 2011)and anoxia (Meyer et al, 2008;Winguth and Winguth, 2012;Grasby et al, 2013).An associated rise in DMS emissions from the ocean and the resulting increase in cloud albedo by higher CCN concentrations would counteract the warming and weathering (Fig. 10).…”
Section: Discussionmentioning
confidence: 99%
“…At Meishan the most dominant PAH are the 3- and 4-ring unsubstituted PAHs such as phenantrene, chrysene and benzo(e)pyrene, while the HMW PAHs (including coronene) occur in very low abundance. A volcanic link for fly-ash occurrences in Arctic Canada (Grasby, Sanei & Beauchamp, 2011) has recently been called into question by Hudspith, Rimmer & Belcher (2014) based on observations that peat-burning can also produce similar vesiculated chars. It should however be stressed that massive flood basalt volcanism producing pyrogenic substances (PAH, soot) does not exclude the simultaneous raging of forest fires; in some instances, volcanism is in fact the likely trigger for widespread forest fires.…”
Section: The Continentsmentioning
confidence: 99%
“…Since Scott (2000) published a seminal review of the up to then accumulated knowledge about pre-Quaternary palaeowildfires, in which was reported that only scattered data would hint at Permian fires, many studies on Permian wildfires, primarily with a focus on the northern hemisphere, have added a lot of knowledge about the issue (e.g. Wang and Chen, 2001;Uhl and Kerp, 2003;Noll et al, 2003;Uhl et al, 2004Uhl et al, , 2008Uhl et al, , 2012DiMichele et al, 2004;Shen et al, 2011Shen et al, , 2012Shao et al, 2012;Hudspith et al, 2012Hudspith et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%